2017
DOI: 10.1155/2017/9614938
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cytological Sampling on EGFR Mutation Testing in Stage III-IV Lung Adenocarcinoma

Abstract: Objectives. There have been advances in the identification and understanding of molecular subsets of lung cancer, defined by specific oncogenic aberrations. A number of actionable genetic alterations have been identified, such as the epidermal growth factor receptor (EGFR) mutation. We aimed to establish the reasons why patients were not undergoing EGFR mutation testing at the time of histological diagnosis. Methods. The records of 70 patients with advanced adenocarcinoma of the lung managed through a single m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Liu et al showed a sensitivity of 81.8% and specificity of 80% for EGFR mutation detection in effusion sample with tissue biopsy sample [12]. Davies et al had successful EGFR mutation analysis in nine of 10 (90%) cases with malignant pleural effusion [14]. Liu et al studied 192 paired malignant effusion and biopsy and found a higher mutation rate in biopsy of 62% compared to effusion of 58.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al showed a sensitivity of 81.8% and specificity of 80% for EGFR mutation detection in effusion sample with tissue biopsy sample [12]. Davies et al had successful EGFR mutation analysis in nine of 10 (90%) cases with malignant pleural effusion [14]. Liu et al studied 192 paired malignant effusion and biopsy and found a higher mutation rate in biopsy of 62% compared to effusion of 58.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Initial tumor testing for EGFR or other mutations is routinely undertaken using direct biopsy of the tumor 10 , 11 ; however, around 30% of NSCLC patients may be unable to provide a biopsy sample that is suitable for EGFR mutation analysis at diagnosis or following disease progression. 11 13 In addition, tissue biopsies, particularly re-biopsies at the point of progression on initial treatment, are invasive and costly, and therefore not always feasible. 10 , 11 , 14 16 Given these drawbacks, the less invasive liquid biopsy may be preferred over traditional tumor biopsy, particularly in monitoring for resistance.…”
Section: Advances In Egfr Mutation Testingmentioning
confidence: 99%
“…The role of cytopathology is gaining importance with the increasing use of minimally invasive techniques like endobronchial ultrasound-guided fine-needle aspiration (EBUS FNA) which can frequently provide adequate material for diagnosis, immunohistochemistry, and mutation analysis [51]. In a study conducted by Rhian et al for assessing the impact of cytological sampling on EGFR mutation testing in stage III-IV lung adenocarcinoma, it was found that cytological sampling was almost as effective as histological methods at acquiring adequate samples for analysis [52]. Current recommendations suggest that molecular analysis be conducted on highly sensitive polymerase chain reaction (PCR) based methods and/or FISH on lung cytology.…”
Section: Role Of Lung Cytology In Lung Cancer Diagnosismentioning
confidence: 99%